EFFECTS OF THE DISPERSAL ALLERGIC POLLEN ON THE HUMAN HEALTH IN Dr.B.R AMBEDKAR OPEN UNIVERSITY, JUBILEEHILLS HYDERABAD, TELANGANA (International Journal of Food and Nutritional Sciences, 2021)
The present study is helpful for analysis of air borne pollen of 18 plant taxa that were recorded in Dr.B.R.Ambedkar open university(Dr.BRAOU). The university is located at Jubilee Hills (spread over 53.63 acres coordinates Latitude: 17.4315 Longitude: 78.4197). The pollen from 08 spider web samples were collected during 2021-2022 from study area and processed by using HCL,HF and acetolysis technique with standard methods (Bera et al., 2002). In this study the following allergic pollen were recorded viz.,,Acanthaceae type,Ageratum conyzoides L,Albizia lebbek.L.,Alternanthera sessilis(L.) R.Br. ex DC,Artemesia vulgaris L.Aevera lanata(L.) Juss. ex Schult.,Azadirachta indica A.Juss.,Eucalyptus globulus Labill.,Jatropha gossypifolia L.,Mangifera indica L.Nerium oleander L.Partheniumhysterophorus L.,Peltophorum pterocarpum (DC.)K.Heyne,Plumbago auriculata Lam., and ,Prosopis juliflora (Sw.) DC.,Syzygium cumini (L.) Skeels, Tridax procumbens L.Tabebuia rosea DC. These allergic pollen affects on human health and causes allergic disorders such as Congestion or runny nose, dry cough, respiratory problems, asthma and rhinitis, hay fever/pollinosis